Odpowiedzi

Najlepsza Odpowiedź!
2010-01-17T19:11:45+01:00
A)
(4-1i1/4:1i9/16)*(-15i5/8)=
=(4 - 5/4 : 25/16) * (-125/8) =
= (4 - 5/4 * 16/25) * (-125/8) =
= (4 - 4/5) * (-125/8) =
= (3 i 1/5) * (-125/8) =
= 16/5 * (-125/8) =
= - 50

b)
2i2/3-25:12,5:(9-6*1i1/6)*(-2)=
= 2 i 2/3 - 25 : 12,5 : (9 - 6 * 7/6) * (-2)=
= 2 i 2/3 - 25 : 12,5 : (9 - 7) * (-2) =
= 2 i 2/3 - 2 : 2 * (-2) =
= 2 i 2/3 - 1 * (-2) =
= 2 i 2/3 + 2 = 4 i 2/3

c)
4/5-(1,2*5/12-0,8):(-1/8)=
= 4/5 - (12/10 * 5/12 - 8/10) : (-1/8) =
= 4/5 - (5/10 - 8/10) : (-1/8) =
= 4/5 - (-3/10):(-1/8) =
= 4/5 - (-3/10)*(-8) =
= 4/5 - 24/10 =
= 8/10 - 24/10 = -16/10 = -1 i 3/5

d)
4,5*1i2/3-3,75:5/9-10/27:(-5/6)=
= 9/2 * 5/3 - 15/4 : 5/9 - 10/27 : (-5/6) =
= 15/2 - 15/4 * 9/5 - 10/27 * (-6/5) =
= 15/2 - 27/4 + 4/9 =
= 7 i 1/2 - 6 i 3/4 + 4/9 =
= 7 i 2/4 - 6 i 3/4 + 4/9 =
= 6 i 6/4 - 6 i 3/4 + 4/9 =
= 3/4 + 4/9 =
= 27/36 + 16/36 = 43/36 = 1 i 7/36




1 5 1